2015
DOI: 10.1126/scitranslmed.aaa2327
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of the NKp30/B7-H6 axis in high-risk neuroblastoma patients

Abstract: The immunosurveillance mechanisms governing high-risk neuroblastoma (HR-NB), a major pediatric malignancy, have been elusive. We identify a potential role for natural killer (NK) cells, in particular the interaction between the NK receptor NKp30 and its ligand, B7-H6, in the metastatic progression and survival of HR-NB after myeloablative multimodal chemotherapy and stem cell transplantation. NB cells expressing the NKp30 ligand B7-H6 stimulated NK cells in an NKp30-dependent manner. Serum concentration of sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
130
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(138 citation statements)
references
References 56 publications
7
130
1
Order By: Relevance
“…27 Semeraro M et al demonstrated that serum concentration of soluble B7-H6 correlated with the downregulation of NKp30, bone marrow metastases and chemoresistance of high-risk neuroblastoma (HR-NB), and they also indicated that soluble B7-H6 contained in the serum of HR-NB patients inhibited NK cell functions in vitro. 28 Together, our results support a notorious role of B7-H6 in the progression of certain types of cancer. Hence, we conclude that the outcome of B7-H6 expression might vary by cancer type.…”
Section: Discussionsupporting
confidence: 62%
“…27 Semeraro M et al demonstrated that serum concentration of soluble B7-H6 correlated with the downregulation of NKp30, bone marrow metastases and chemoresistance of high-risk neuroblastoma (HR-NB), and they also indicated that soluble B7-H6 contained in the serum of HR-NB patients inhibited NK cell functions in vitro. 28 Together, our results support a notorious role of B7-H6 in the progression of certain types of cancer. Hence, we conclude that the outcome of B7-H6 expression might vary by cancer type.…”
Section: Discussionsupporting
confidence: 62%
“…6,7 NKp30 possesses alternatively spliced isoforms, which are of prognostic value for patients with gastrointestinal stromal tumors 8 and for patients with high risk neuroblastoma responding to induction chemotherapy. 9 Intriguingly, the initially described ligands for NKp30, the human cytomegalovirus pp65 tegument protein 10 and the HLA-B-associated transcript 3 (BAT3) protein 11 , were both intracellular proteins. B7-H6 (Natural cytotoxicity triggering receptor 3 ligand 1, NCR3LG1) was the first NKp30-ligand identified being a transmembrane protein expressed on tumor cell surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Quantification of serum concentration of soluble B7-H6, ligand of NKp30 activation molecule, correlated with the downregulation of NKp30, bone marrow metastasis, and chemoresistance [14]. Thus, interaction between NKp30 and B7-H6 may contribute to neuroblastoma immunosurveillance and both NKp30 expression on circulating NK cells and the serum concentration of soluble B7-H6 may represent biomarkers for risk stratification [14].…”
Section: Immunotherapy Of Neuroblastomamentioning
confidence: 99%